European evidence-based recommendations for the diagnosis and treatment of childhood-onset lupus nephritis: the SHARE initiative. Issue 12 (6th September 2017) - Groot, Noortje; de Graeff, Nienke; Marks, Stephen D; Brogan, Paul; Avcin, Tadej; Bader-Meunier, Brigitte; Dolezalova, Pavla; Feldman, Brian M; Kone-Paut, Isabelle; Lahdenne, Pekka; McCann, Liza; Özen, Seza; et al.
Abstract : Lupus nephritis (LN) occurs in 50%–60% of patients with childhood-onset systemic lupus erythematosus (cSLE), leading to significant morbidity. Timely recognition of renal involvement and appropriate treatment are essential to prevent renal damage. The Single Hub and Access point for paediatric Rheumatology in Europe (SHARE) initiative aimed to generate diagnostic and management regimens for children and adolescents with rheumatic diseases including cSLE. Here, we provide evidence-based recommendations for diagnosis and treatment of childhood LN. Recommendations were developed using the European League Against Rheumatism standard operating procedures. A European-wide expert committee including paediatric nephrology representation formulated recommendations using a nominal group technique. Six recommendations regarding diagnosis and 20 recommendations covering treatment choices and goals were accepted, including each class of LN, described in the International Society of Nephrology/Renal Pathology Society 2003 classification system. Treatment goal should be complete renal response. Treatment of class I LN should mainly be guided by other symptoms. Class II LN should be treated initially with low-dose prednisone, only adding a disease-modifying antirheumatic drug after 3 months of persistent proteinuria or prednisone dependency. Induction treatment of class III/IV LN should be mycophenolate mofetil (MMF) or intravenous cyclophosphamide combined with corticosteroids; maintenance treatment should be MMF or azathioprine for at least 3 years. In pure class V LN, MMF with low-dose prednisone can be used as induction and MMF as maintenance treatment. The SHARE recommendations for diagnosis and treatment of LN have been generated to support uniform and high-quality care for all children with SLE.